Analysis of Entrepreneurial Orientation and Innovation Capability On Competitive Advantage (Study on Satay Culinary MSMEs Registered at DPMPTSP in Sukabumi City) - Nadella Nur Fitria; Faizal Mulia; Sopyan Saori (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy. One of the fastest-growing sectors within the MSME category is the culinary industry, including satay businesses, which are a traditional food with high market demand. Sukabumi City, as one of the developing cities in West Java, has many satay culinary MSMEs registered with the Investment and One-Stop Integrated Services Office (DPMPTSP). However, the increasingly intense competition requires MSME actors to possess competitive advantages in order to survive and grow.The purpose of this research is to examine the effect of Entrepreneurial Orientation and Innovation Capability on Competitive Advantage. This study was conducted on satay culinary MSMEs registered with the DPMPTSP of Sukabumi City, involving 86 business owners as respondents. A multiple linear regression analysis approach was used as the research method. The research results, based on SPSS 25 calculations and analysis, indicate that Entrepreneurial Orientation has a positive and significant effect on Competitive Advantage. Furthermore, Innovation Capability also has a positive and significant effect on Competitive Advantage.